2014
DOI: 10.4172/2155-9899.1000273
|View full text |Cite
|
Sign up to set email alerts
|

Bifunctional Peptide Inhibitors Suppress Interleukin-6 Proliferation and Ameliorates Murine Collagen-Induced Arthritis

Abstract: The objective of this study is to evaluate the efficacy and potential mechanism of action of type-II collagen bifunctional peptide inhibitor (CII-BPI) molecules in suppressing rheumatoid arthritis in the collagen-induced arthritis (CIA) mouse model. CII-BPI molecules (CII-BPI-1, CII-BPI-2, and CII-BPI-3) were formed through conjugation between an antigenic peptide derived from type-II collagen and a cell adhesion peptide LABL (CD11a237-246) from the I-domain of LFA-1 via a linker molecule. The hypothesis is th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 58 publications
(72 reference statements)
0
2
0
Order By: Relevance
“…37 In addition, CII-BPI molecules that are conjugates between LABL and collagen-II peptides suppressed rheumatoid arthritis (RA) in collageninduce arthritis (CIA) mice. 38 The concept of BPI was extended to protein and polymer conjugates such as Fc-BPI, I-domain antigen conjugate (IDAC), and soluble antigen array (SAgA) molecules; they are composed of LABL and antigenic peptides. 31 These large conjugates have been shown to effectively suppress EAE in the mouse model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…37 In addition, CII-BPI molecules that are conjugates between LABL and collagen-II peptides suppressed rheumatoid arthritis (RA) in collageninduce arthritis (CIA) mice. 38 The concept of BPI was extended to protein and polymer conjugates such as Fc-BPI, I-domain antigen conjugate (IDAC), and soluble antigen array (SAgA) molecules; they are composed of LABL and antigenic peptides. 31 These large conjugates have been shown to effectively suppress EAE in the mouse model.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work has implied that LABL-antigenic peptide conjugates can alter autoimmune inflammatory response to an antigenspecific tolerogenic responses. 31,[35][36][37][38] Our previous work had shown that cLABL peptide (cyclo1,12-PenITDGEATDSGC) derived from the LFA-1 I-domain interacted with the ICAM-1 D1 domain 23,39 to inhibit adhesion of lymphocytes 29,30 in an in vitro model of epithelial cell inflammation. 22 This peptide was synthesized by incorporating cysteine (Cys) and penicillamine (Pen) residues to the C-and N-termini, respectively, on the Ile 237 -Gly 246 sequence of the I-domain.…”
Section: Introductionmentioning
confidence: 99%